Prefabricated Vertical Drain (PVD) and Deep Cement Mixing (DCM)/Stiffened DCM (SDCM) techniques for soft ground improvement - D T Bergado; P V Long; S Chaiyaput; A S Balasubramaniam (My University, 2018)
Soft ground improvement techniques have become most practical and popular methods to increase soil strength, soil stiffness and reduce soil compressibility including the soft Bangkok clay. This paper focuses on comparative performances of prefabricated vertical drain (PVD) using surcharge, vacuum and heat preloading as well as the cement-admixed clay of Deep Cement Mixing (DCM) and Stiffened DCM (SDCM) methods. The Vacuum-PVD can increase the horizontal coefficient of consolidation, Ch, resulting in faster rate of settlement at the same magnitudes of settlement compared to Conventional PVD. Several field methods of applying vacuum preloading are also compared. Moreover, the Thermal PVD and Thermal Vacuum PVD can increase further the coefficient of horizontal consolidation, Ch, with the associated reduction of kh/ks values by reducing the drainage retardation effects in the smear zone around the PVD which resulted in faster rates of consolidation and higher magnitudes of settlements. Furthermore, the equivalent smear effect due to non-uniform consolidation is also discussed in addition to the smear due to the mechanical installation of PVDs. In addition, a new kind of reinforced deep mixing method, namely Stiffened Deep Cement Mixing (SDCM) pile is introduced to improve the flexural resistance, improve the field quality control, and prevent unexpected failures of the Deep Cement Mixing (DCM) pile. The SDCM pile consists of DCM pile reinforced with the insertion of precast reinforced concrete (RC) core. The full scale test embankment on soft clay improved by SDCM and DCM piles was also analysed. Numerical simulations using the 3D PLAXIS Foundation finite element software have been done to understand the behavior of SDCM and DCM piles. The simulation results indicated that the surface settlements decreased with increasing lengths of the RC cores, and, at lesser extent, increasing sectional areas of the RC cores in the SDCM piles. In addition, the lateral movements decreased by increasing the lengths (longer than 4 m) and, the sectional areas of the RC cores in the SDCM piles. The results of the numerical simulations closely agreed with the observed data and successfully verified the parameters affecting the performances and behavior of both SDCM and DCM piles.
Keywords: Consolidation; Precast concrete; Geotechnical Engineering and Soil Stabilization